VARIASI BAHASA YANG DIGUNAKAN OLEH KALANGAN WARIA KOTA MERAUKE - Narahawarin, Margaretha F.; Winarsih, Sri; Bawawa, Marni (Kajian Linguistik, 2019)
Variation of languages used transvestites in Merauke city to interacting is very unique and very interesting to study, because in daily communication transvestites often change (switch) languages, from one to another language so this research aims to classify the variation of languages and their functions used by transvestites of Merauke city.This research is a qualitative descriptive study with object of the research is transvestites as informants. Data collection techniques usesociolinguistic research are observe critically method, survey method, and interview method. The data analysis technique was performed using the analysis model by Miles and Huberman namely data reduction, data display, and verification.The results showed that based on the classification in variations of language used by transvestites are: 1) jargon, 2) slang, 3) acronyms, and 4) forms of puns. Whereas the function of language variation used by transvestites are: 1) creating humor, 2) insinuating or mocking, 3) intimidating / familiarizing the relationship, 4) keeping to certain information, 5) refined to something that considered vulgar or taboo, and 6) expressing attitude and feelings of the heart. Keywords: variation of language, function of language variation,transvestites